Urgency enforces stimulus-driven action across spatial and numerical cognitive control tasks. - Anika Krause; Christian H Poth (PLoS ONE)
It has been shown that urgency in cognitive control tasks elicits a time-window in which responses are dominated by stimuli rather than goals. If stimulus information conflicts with goal-relevant information, urgency impairs goal-directed responses. This was shown for an antisaccade task as well as tasks using manual responses. Critically, however, all previous studies on manual responses used arrows as stimuli, leaving it unclear whether urgency affects cognitive control also in tasks using different stimuli. Here, we show that the urgency effect can also be elicited in three cognitive control tasks that do not use arrow stimuli. Participants completed either a Spatial Stroop task with word stimuli, in which they reacted to the word meaning while ignoring the spatial position, or a Numerical Stroop Task, in which they had to respond to the numerically larger of two presented numbers. The physical size of the numbers varied but was irrelevant to the task. The third task was a Simon task, where participants were instructed to react to the color of a stimulus while ignoring its spatial position. In all tasks, urgency evoked a time window, in which the position or the physical size dominated the response, which was evident from a drop of performance below chance level in conflict situations. These results reveal that the effect of urgency on cognitive control does not depend on arrow stimuli and emerges in a number of other spatially related tasks, specifically in spatial and numerical cognitive control tasks. As such, they suggest that urgency affects cognitive control more generally.